AIP-based Professional Intervention Program for Adversity for trauma and stress reduction in groups: a pilot study in Ethiopia - Woldemariam, Solomon; Ashman, Dorothy; Carvalho, Esly; Wong, Sik-Lam; Hoersting, Raquel (Frontiers in Psychiatry, 2024)
Drawing from the principles of EMDR therapy and the AIP model, the Professional Intervention Program for Adversity (PIPA) was developed with the objective of amalgamating low-intensity group exercises into a unified framework, as a comprehensive intervention for group therapy. The PIPA Program integrates various aspects of EMDR therapy—such as stabilization, resourcing, desensitization, reprocessing, and forming beliefs about the self and future—into a cohesive program. The program's structure includes self-regulation exercises, the Pillars of Life, the Flash Technique, and the Quadrants exercise. The PIPA Program was administered to more than 220 individuals with a high probability of traumatization by the two-year civil war in Ethiopia (2020-2022). The results of this study show a significant improvement in PTSD symptoms and distress levels after completing the PIPA Program in a pre- and post-test design. Future studies should explore the long-term effects of the PIPA Program and its broader application across different therapeutic contexts. The findings suggest that the PIPA Program is a promising group-based intervention for trauma treatment that is safe and effective, especially in non-clinical settings and for culturally diverse populations.